2018
DOI: 10.1101/293282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Terrestriality and bacterial transfer: A comparative study of gut microbiomes in sympatric Malagasy mammals

Abstract: 17The gut microbiomes of mammals appear to mirror their hosts ' phylogeny, 18 suggesting a shared history of co-speciation. Yet

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 95 publications
3
18
0
Order By: Relevance
“…We specifically showed that both constraints shape GMB membership but the phylogenetic scale of analyses can influence the results and their interpretation. Our findings are consistent with recent reports across mammals (Groussin et al, ; Ley et al, ; Nishida & Ochman, ; Perofsky et al, ) and primates (Amato et al, ), including lemurs (Greene et al, in review), that, at gross scales and when feeding strategies are convergent, phylogeny is a strong predictor of GMB structure. Nevertheless, when examining dynamics within lineages of folivores or herbivores compared with frugivores or omnivores, feeding strategy more strongly underlies host–microbiome coadaptation.…”
Section: Study 3 Beyond the Gut: Scent‐gland Microbiomes Vary By Bodsupporting
confidence: 93%
See 2 more Smart Citations
“…We specifically showed that both constraints shape GMB membership but the phylogenetic scale of analyses can influence the results and their interpretation. Our findings are consistent with recent reports across mammals (Groussin et al, ; Ley et al, ; Nishida & Ochman, ; Perofsky et al, ) and primates (Amato et al, ), including lemurs (Greene et al, in review), that, at gross scales and when feeding strategies are convergent, phylogeny is a strong predictor of GMB structure. Nevertheless, when examining dynamics within lineages of folivores or herbivores compared with frugivores or omnivores, feeding strategy more strongly underlies host–microbiome coadaptation.…”
Section: Study 3 Beyond the Gut: Scent‐gland Microbiomes Vary By Bodsupporting
confidence: 93%
“…Researchers have documented within‐species variation in GMB structure relative to seasonal food availability (Springer et al, ), habitat quality (Bennett et al, ), and social dynamics (Perofsky, Lewis, Abondano, Di Fiore, & Meyers, ; Raulo et al, ). Increasingly, researchers have adopted small‐scale comparative approaches, investigating GMB composition across host populations, species, and habitat types (Greene et al, in review; Perofsky, Lewis, & Meyers, ; Umanets et al, ). Opportunities for longitudinal sampling and experimental manipulation using captive populations have facilitated studies on the timing of microbiome acquisition across host ontogenetic development (McKenney, Rodrigo, & Yoder, ), patterns of recovery from enteric infection (McKenney, Greene, Drea, & Yoder, ), and response to changing dietary quality (Greene, McKenney, O'Connell, & Drea, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) or even at a similar level in the forest canopy (Perofsky et al . ) converge in their microbiota, community composition remains most strongly predicted by species identity. By contrast, studies on the gut microbiota of distantly related artiodactyl species (Moeller et al .…”
Section: Discussionmentioning
confidence: 99%
“…An insu cient supply with these materials causes an impairment of ruminal development and, in consequence, a reduced (microbial) digestive capacity [3]. Another important factor is the GIT microbiome itself, which is believed to be shaped by animal genetics, diet, environmental (geographic) parameters [4], and social contact patterns [5,6,7].…”
Section: Introductionmentioning
confidence: 99%